Mobile messaging technologies and services : SMS, EMS, and MMS - Le Bodic, Gwenaël (J. Wiley & Sons, 2005)
Mobile Messaging Technologies and Services provides an in-depth description of existing and forthcoming messaging services and underlying technologies. The Short Message Service (SMS) has been a tremendous success in the messaging roadmap and the recently introduced Enhanced Messaging Service (EMS), an application-level extension of SMS, is expected to offer a smooth transition to the forthcoming Multimedia Messaging Service (MMS).